Peran Pemerintah Desa dalam Pengembangan Sumber Daya Manusia di Desa Lasori Kecamatan Mawasangka Timur Kabupaten Buton Tengah - La Ode Raffjany Rangsha Vany; Nastia Nastia; Muh Askal Basir (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
The purpose of this study is the role of the village government in developing human resources in Lasori Village, East Mawasangka District, Central Buton Regency. The type of research used in this research is descriptive research with a qualitative approach. Data collection techniques namely Observation, Interview, Documentation and Literature Study. Data analysis techniques in research are data reduction, data presentation, and drawing conclusions. The results obtained in this study are the role of the government in Lasori Village, Mawasangka Timur District, Central Buton Regency in developing human resources, including: 1) The government as a facilitator is to create conducive conditions for the implementation of development in order to bridge various community interests in optimizing regional development . With regard to human resource development, the village government facilitates the training community to conduct training, so that the community has good skills and has competitiveness; The government's role as a regulator is to prepare directives to balance the implementation of development through the issuance of regulations. As a regulator, the government provides a basic reference to the community as an instrument to regulate all development implementation activities; The government as a motivator, in forming a society that is obedient and obedient to regulations, the role of local government is needed as a motivator so that it can provide motivation to the community so that people have the will to obey and comply with regulations.